Efficient high-gain low-noise amplifier topologies using GaAs FET at 3.5 GHz for 5G systems - Zarrik, Samia; Bendali, Abdelhak; Fadlaoui, Elmahdi; Benkhadda, Karima; Habibi, Sanae; Kobbi, Mouad El; Sahel, Zahra; Habibi, Mohamed; Hadjoudja, Abdelkader (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Achieving a gain greater than 18 dB with a noise figure (NF) below 2 dB at 3.5 GHz remains a formidable challenge for low-noise amplifiers (LNAs) in sub-6 GHz 5G systems. This study explores and evaluates various LNA topologies, including single-stage designs with inductive source degeneration and cascade configurations, to optimize performance. The single-stage topology with inductive source degeneration achieves a gain of 18.141 dB and an NF of 1.448 dB, while the cascade-stage common-source low-noise amplifier with inductive degeneration achieves a gain of 32.714 dB and a noise figure of 1.563 dB. These results underscore the importance of GaAs FET technology in meeting the demanding requirements of 5G systems, specifically in the 3.5 GHz frequency band. The advancements demonstrated in gain, noise figure, and linearity affirm the viability of optimized LNA topologies for high-performance 5G applications, supporting improved signal quality and reliability essential for modern telecommunication infrastructure.